2013
DOI: 10.1021/cb300584e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interrogation of the Neuronal Kinome Using a Primary Cell-Based Screening Assay

Abstract: A fundamental impediment to functional recovery from spinal cord injury (SCI) and traumatic brain injury is the lack of sufficient axonal regeneration in the adult central nervous system. There is thus a need to develop agents that can stimulate axon growth to re-establish severed connections. Given the critical role played by protein kinases in regulating axon growth and the potential for pharmacological intervention, small molecule protein kinase inhibitors present a promising therapeutic strategy. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 47 publications
2
64
0
Order By: Relevance
“…The previous observation, along with the fact that JUN has been implicated in peripheral nerve regeneration, led us to further test JUN’s role in CNS axon growth, using an organotypic cortical slice model (Blackmore, et al, 2012; Al-Ali, et al, 2013). In this model PN5 cortical slices are “matured” for 1 week in vitro, after which they are injured by transection, and transected halves are allowed to fuse (Figure 3A and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The previous observation, along with the fact that JUN has been implicated in peripheral nerve regeneration, led us to further test JUN’s role in CNS axon growth, using an organotypic cortical slice model (Blackmore, et al, 2012; Al-Ali, et al, 2013). In this model PN5 cortical slices are “matured” for 1 week in vitro, after which they are injured by transection, and transected halves are allowed to fuse (Figure 3A and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…An overexpression screen using embryonic hippocampal neurons was used to identify KLF4, a member of the KLF family of transcription factors, as a developmental regulator of axon growth 25 . Small molecule screens with these neurons have also identified kinase inhibitors that were later shown to promote regeneration of axons in cortical slice cultures and of CST axons in vivo 43,86 . Overexpression, biochemical, and computational studies have found that many of the kinases that regulate neurite outgrowth in other CNS neurons also regulate neurite outgrowth in hippocampal neurons 42,43 .…”
Section: A Low-density (Sparse) Culture Modelsmentioning
confidence: 99%
“…With tools like genetic fate mapping and viral vectors, it is possible to observe growing axons without classical antero- or retrograde tracers 86,192 . In recent years, cortical slice cultures have been used to study axon regrowth following manipulations of regeneration associated transcription factors 193 .…”
Section: Explant/organotypic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in high-content imaging technologies make it possible to characterize large numbers of compounds by the morphological changes that they induce in cells, as captured by automated microscopy. Descriptive features such as cell or organelle size, shape and intensity are extracted by image processing software and give rise to phenotypic profiles [36,37] that have successfully been used to classify small molecules by their mechanistic class, define the role of a particular drug target, if multiple structurally diverse ligands produced the same phenotype, and identify compounds with unintended cellular activities within a chemical series [38][39][40][41][42].…”
Section: Moa Elucidationmentioning
confidence: 99%